Conservative treatment of splenic infarction and intestinal obstruction caused by a wandering spleen. Issue 2 (May 2014) - Ihedioha, U; Syed, A; Lloyd, G; Scott, A
The underdevelopment or absence of the splenic suspensary ligaments can lead to an uncommon condition termed the wandering spleen. It is usually asymptomatic but can present with an acute abdomen when associated with torsion. Most authors advocate surgical treatment. Herein, we report a case of torsion with infarction of the spleen and intestinal obstruction in a 36-year-old female patient which was successfully managed conservatively.